IMPLEMENTASI PROGRAM JAMINAN SOSIAL KETENAGAKERJAAN BAGI PEKERJA SEKTOR INFORMAL DI KOTA YOGYAKARTA - Yoga Adi Purnamasari; Sri Suwitri (Journal of Management and Public Policy, 2026)
This study examines the implementation of the Employment Social Security program for informal- sector workers in Yogyakarta City and identifies key obstacles affecting its delivery. The research is grounded in the situation of informal workers who often lack employment certainty and have limited access to formal labor protection and social security. The study aims to describe how the program (particularly work accident, death, and old-age benefits) is implemented and to assess implementation dynamics using Merilee S. Grindle’s framework (content of policy and context of implementation), while obstacles are analyzed through the themes of communication, resources, implementers’ disposition, and bureaucratic structure. A descriptive qualitative approach is applied, using interviews, observations, and documentation; conclusions are drawn and verified by cross-checking evidence across different sources. Findings indicate that implementation has been carried out and shows adaptive efforts to reach heterogeneous informal workers by combining in-office services with digital channels, outreach (“jemput bola”), and partnerships with communities/actors closely connected to workers, which helps expand registration access when procedures run smoothly. However, membership sustainability is the most vulnerable aspect, shaped by income stability, service experiences, and workers’ trust in the ease of accessing benefits when needed. The most visible barriers lie in communication and participants’ understanding information is available through multiple channels but is unevenly distributed and often too technical or inconsistent. Other interrelated constraints include limited time and economic capacity to follow procedures, technical issues in digital services, variation in service responsiveness and explanation quality, and less flexible follow-up processes (e.g., data correction, reactivation, and claims) due to multi-step approvals and inter-unit coordination needs.